SIMULASI ANALISIS KORESPONDENSI UNTUK DATA TRACER STUDI DI TINGKAT SEKOLAH MENENGAH [SIMULATION OF A CORRESPONDENCE ANALYSIS FOR A TRACER STUDY WITH HIGH SCHOOL ALUMNI] - Yohansa, Meicheil (JOHME: Journal of Holistic Mathematics Education, 2018)
A Tracer Study is research or a study of alumni tracking. Graduates or alumni are considered to have the most appropriate capacity to provide feedback as far as an evaluation of the institution is concerned. That is why the implementation of a Tracer Study is often attributed to the efforts of evaluation and improvement of the education system of an institution. Through the implementation of a Tracer Study, institutions can obtain information about possible deficiencies in the educational and learning process. In Indonesia, a Tracer Study is generally implemented to track alumni of a university and their associations in the working world. By seeing the usefulness of a Tracer Study at the university level, this study conducted an implementation of a Tracer Study at the high school level. The implementation itself focused on the determination of the respondent and the preparation of the questionnaire as a research instrument by accounting for the differences in the characteristics of high school and university graduates. The Tracer Study results were analyzed using correspondence analysis with Eigenvalue Decomposition (EVD). Data analysis was carried out on a case study about the relationship between non-academic activities and communication capabilities.BAHASA INDONESIA ABSTRAK: Tracer Study dikenal sebagai suatu penelitian atau studi mengenai pelacakan alumni. Sedangkan alumni itu sendiri dianggap memiliki kapasitas yang paling tepat dalam memberikan umpan balik sebagai evaluasi terhadap institusi yang bersangkutan. Sehingga pada pelaksanaannya Tracer Study kerap kali dikaitkan dengan upaya evaluasi serta perbaikan sistem pendidikan dari suatu institusi. Melalui pelaksanaan Tracer Study, lembaga penyelenggara pendidikan memungkinkan untuk memperoleh informasi kemungkinan kekurangan dalam proses pendidikan dan pembelajaran. Di Indonesia, Tracer Study umumnya dilaksanakan untuk melacak alumni dari suatu perguruan tinggi dengan asosiasi terhadap dunia industri kerja. Melihat gambaran kebermanfaatan Tracer Study di beberapa perguruan tinggi, maka pada penelitian ini dilakukan adaptasi Tracer Study untuk dilaksanakan pada tingkat satuan pendidikan sekolah menengah atas (SMA). Adaptasi pelaksanaan Tracer Study di SMA menitikberatkan pada penentuan responden dan penyusunan kuesioner sebagai instrumen penelitian. Hal ini sebagai akibat dari perbedaan karakteristik lulusan SMA dan perguruan tinggi. Hasil Tracer Study dianalisis menggunakan Analisis Korespondensi dengan dekomposisi nilai eigen. Analisis data dilakukan terhadap studi kasus mengenai hubungan antara kegiatan non akademik dengan kemampuan komunikasi.